Production of Indole-3-Lactic Acid by Bifidobacterium Strains Isolated fromHuman Infants - Takuma Sakurai; Toshitaka Odamaki; Jin-zhong Xiao (Microorganisms, 2019)
Recent studies have shown that metabolites produced by microbes can be considered as mediators of host-microbial interactions. In this study, we examined the production of tryptophan metabolites by Bifidobacterium strains found in the gastrointestinal tracts of humans and other animals. Indole-3-lactic acid (ILA) was the only tryptophan metabolite produced in bifidobacteria culture supernatants. No others, including indole-3-propionic acid, indole-3-acetic acid, and indole-3-aldehyde, were produced. Strains of bifidobacterial species commonly isolated from the intestines of human infants, such as Bifidobacterium longum subsp. longum, Bifidobacterium longum subsp. infantis, Bifidobacterium breve, and Bifidobacterium bifidum, produced higher levels of ILA than did strains of other species. These results imply that infant-type bifidobacteria might play a specific role in host−microbial cross-talk by producing ILA in human infants.